HAK ASASI MANUSIA DALAM ISLAM - Laila Rahmawati (POSTGRADUATE OF PALANGKA RAYA STATE ISLAMIC INSTITUTION, 2017)
This article tries to describe the concept of Human Rights in the West and the response of Islam to them. In its history, it was Magna Charta in England that initiated the formulation of Human Rights in the West in 1512. Then It was followed by The Bill of right in 1689; The American Declaration of Independence in 1776; and The French Declaration in 1789 that resulted in The rule of law. Human Rights entered a new phase after The United Nations had declared the International Human Rights in1984, that is The Universal Declaration of Human Rights. From that time on, Human Rights has become a global issue, continually discussed and responded to by many including Muslim scholars. In the West, the concept of Human Right is based merely on human values (anthropocentric) so that the responsibility is restricted to human beings. Based on this, this concept is different from Islamic concept on Human Rights because the former is based on secular values while the later is based on human values and divine values. Normatively, the idea of Human Rights is relevant to Islamic idea. The reason is that, based on their fitrah as creatures, human beings extremely expect the maintenance of their main needs (Al- umur al-Daruriyyah). Therefore, Human Rights are suitable with the purpose of syari’ah (maqasid al-Syari), that is to maintain religion, reason, heredity dan property.